Management of small cell lung cancer complicated with paraneoplastic Cushing’s syndrome: a systematic literature review - Li, Yanlong; Li, Caiyu; Qi, Xiangjun; Yu, Ling; Lin, Lizhu (Frontiers in Endocrinology, 2023)
Paraneoplastic Cushing´s syndrome (PCS) is a rare, but clinically important feature of small cell lung cancer (SCLC), that is associated with even worse prognosis. To identify key considerations in comprehensive management of SCLC patients complicated with PCS, we conducted a systematic review of relevant reports on PubMed and Web of Science, focusing on SCLC with PCS cases. The systematic review analyzed 61 reports published between 1985 and 2022 with a total of 157 SCLC patients included. Out of the 157 patients, 132 (84.1%) patients across 58 (95.1%) reports were diagnosed with ectopic Cushing's syndrome. The immunohistochemical (IHC) staining for adrenocorticotropic hormone (ACTH) was performed on 30 (19.1%) patients across 22 (36.1%) reports and demonstrated encouraging performance. For treatment, chemotherapy and ketoconazole were utilized in 50 (81.97%) and 24 (39.34%) reports, respectively. Regarding cause of death, infection and cancer were equally frequent, each being recorded in 17 (27.87%) reports. To conclude, the majority of PCS cases in SCLC patients were caused by ectopic hormone secretion. In order to make a differential diagnosis, it is recommended to utilize IHC staining for a specific hormone such as ACTH or corticotropin-releasing hormone. In comprehensive treatment of SCLC with PCS patients, effective management of hypercortisolism and potent safeguarding against infection play as two crucial roles. Ultimately, further confirmations are required regarding the specificity and accuracy of IHC staining technique as well as the efficacy and safety of immunotherapy in the treatment of SCLC with PCS patients.